INTERAKSI GALUR Ã— LINGKUNGAN, POTENSI HASIL DAN STABILITAS HASIL GALUR HARAPAN KEDELAI {GLYCINE MAX (L.) MERR.} HITAM - Adie, M Muchlish; Krisnawati, Ayda; Susanto, GWA (BERITA BIOLOGI, 2013)
Recent demand of black soybean {Glycine max (L.) Merr.} seed has been rising for industrial raw material. A total of five promising lines of black soybean (9837/K-D-8-185, 9837/K-D-3-185-195, W/9837-D-6-220, 9837/K-D-3-185-82 and 9837/W-D-5-211) were evaluated for the potential yield at 18 soybean production centrals in West Java, East Java, Bali and West Nusa Tenggara, from 2004 until 2006..Variety of Cikuray (black soybean), Wilis (famous variety with high yield) and Burangrang (large seed size and short maturation day) were used as check varieties.The field experimental design for each location was completely randomized design with four replicates.The treatment consist of eight lines/variety with 2,4 m × 4,5 m plot size, 40 cm × 15 cm plant distance, two plants/hill.Fertilizer of 50 kg Urea, 100 kg SP36 and 75 kg KCl per ha were applied before sowing time. Weed, insect and disease were controlled intensively.Stability analysis was according to Eberhart and Russell (1966), and adaptability was by Finlay dan Wilkinson (1963). Location, genotype and interaction between 2genotype x environment (G × L) were significant for seed yield. Estimate of environment variance component (d L = 0.0604) was the 2 2 biggest one, and followed by error variance value (d E = 0.0470), genotype variance (d G = 0.0258) and the smallest was estimate of 2 interaction variance G × L (d GL = 0.0225).Significant interaction of G × L showed that each promising lines have specific reaction to certain location quality. Five promising lines were able to produce 2.44 until 2.51 t/ha, or 17% higher than black soybean variety of Cikuray (2.03 t/ha); or 10% higher than Burangrang and 3% more higher than Wilis. Genotype of 9837/K-D-3-185-195, W/9837-D-6-220, 9837/K-D-3-185-82 and 9837/W-D-5-211 were indentified stable. Genotype of 9837/K-D-3-185-195, W/9837-D-6-220, 9837/K-D-3-185-82 and 9837/W-D-5-211 were promising to be high yielded and adaptable across location; on the contrary, genotype of 9837/K-D-8-185 was more adaptable in optimal location.